Analisis Hukum dan Strategi Untuk Menyelesaikan Kasus Geser Hari Libur Tanpa Upah Lembur - Nurhalizah, Aisyah; Hervinia, Helen; Frefy, Fyo Akbar Putra; Benedicta, Liametami; Sembogo, Achmad Dimas Aliffian; Yuli, Yuliana (Media Hukum Indonesia (MHI), 2024)
The case of shifting holidays without overtime pay is a major concern in the field of labor law. This phenomenon raises questions related to the company's compliance with applicable legal provisions and the protection of workers' rights. In this study, we conduct an in-depth analysis of the relevant legal aspects and strategies that can be applied to resolve this type of case. The approach used includes an analysis of applicable labor regulations, case studies to identify patterns of company behavior, and a review of court decisions related to similar cases. The method used in the literature study research is beneficial, namely finding a foundation to obtain and build a theoretical basis, a framework for thinking, and determining temporary research assumptions. The results of the analysis show that there are legal loopholes that allow shifting holidays without overtime pay to occur, but also provide room for the protection of workers' rights. The recommended strategies include increasing legal awareness among workers, strict monitoring of companies' compliance with regulations, and legal advocacy to enforce workers' rights. This study makes an important contribution to understanding and resolving cases of shifting holidays without overtime pay effectively, as well as providing a basis for formulating stronger policies in protecting workers' rights.